LCVD preparation and luminescence properties of Lu2O3:Eu single crystal film. (June 2019) - Feng, He; Chang, Jingyu; Qi, Yunhang; Mao, Rihua; Chen, Bangrui; Yuan, Rui; Xu, Zhan; Zhang, Zhijun; Zhao, Jingtai
Highlights: Lu2 O3 :Eu film was obtained through laser chemical vapor deposition on YSZ single crystal substrate for the first time. The monocrystallinity of as grown film were investigated and confirmed. The preliminary photoluminescence and scintillation properties of Lu2 O3 :Eu single crystal film on YSZ single crystal substrate were reported for the first time. Abstract: Lu2 O3 :Eu scintillation film is one of the most attractive candidate for the hard X-ray imaging, especially in the range of above 30 keV. Single crystal film (SCF) of Lu2 O3 :Eu is difficult to obtain due to its super high melting point. In this letter, transparent Lu2 O3 :Eu SCF with 2.5 μm thickness was firstly obtained by laser chemical vapor deposition on a YSZ (100) single crystal substrate. The crystallinity and morphology of obtained film were investigated by the scan electron microscopy and X-ray diffraction. The photoluminescence and scintillation properties were measured and discussed, including photoluminescence excitation and photoluminescence curves, photoluminescence decay curves, X-ray excited luminescence curve and afterglow curve.